Menebar Perdamaian Dalam Konflik Pembangunan Gereja di Aceh Singkil - Susilawati Panjaitan (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This research was conducted at the HKI Suka Makmur church in building peace in Aceh Singkil. Knowing the factors that limit the suitability index value of the HKI Suka Makmur church in building peace in Greja HKI, the factors that support peace in Greja HKI. The method used in this research is a descriptive, quantitative method. Determining the research location was based on the burning of Greja HKI. This operation resulted in many of Greja HKI being burned.